A Genetically Engineered, Chain Mail‐Like Nanostructured Protein Material with Increased Fatigue Resistance and Enhanced Self‐Healing. Issue 11 (20th January 2022) - Domínguez‐Zotes, Santos; Fuertes, Miguel Angel; Rodríguez‐Huete, Alicia; Valbuena, Alejandro; Mateu, Mauricio G
Abstract: Protein‐based nanostructured materials are being developed for many biomedical and nanotechnological applications. Despite their many desirable features, protein materials are highly susceptible to disruption by mechanical stress and fatigue. This study is aimed to increase fatigue resistance and enhance self‐healing of a natural protein‐based supramolecular nanomaterial through permanent genetic modification. The authors envisage the conversion of a model nanosheet, formed by a regular array of noncovalently bound human immunodeficiency virus capsid protein molecules, into a supramolecular "chain mail." Rationally engineered mutations allow the formation of a regular network of disulfide bridges in the protein lattice. This network links each molecule in the lattice to each adjacent molecule through one covalent bond, analogous to the rivetting of interlinked iron rings in the chain mail of a medieval knight. The engineered protein nanosheet shows greatly increased thermostability and resistance to mechanical stress and fatigue in particular, as well as enhanced self‐healing, without undesirable stiffening compared to the original material. The results provide proof of concept for a genetic design to permanently increase fatigue resistance and enhance self‐healing of protein‐based nanostructured materials. They also provide insights into the molecular basis for fatigue of protein materials. Abstract : A nanostructured protein material is genetically modified to permanently increase its resistance to fatigue and enhance self‐healing. Each protein molecule is mutated to become covalently linked to each adjacent molecule, analogous to the rivetting of iron rings in a medieval knight's chain mail. This genetic approach may be used to build protein‐based nanomaterials and nanodevices that withstand substantial mechanical stress.